Synthesis Of Chitosan Activated Carbon Composite For Adsorption Of Brilliant Black Bn Dye From Aqueous Solution - Razam, Muhammad Azrie (Universiti Sains Malaysia, 2021)
Water pollution is one of the biggest disasters that can endangered the aquatic ecosystem and human civilization if it did not been treated accordingly. One of the factors that contribute to the water pollution is by the contamination of dye due to it is high stability properties towards light, temperature, detergents, chemicals, bleaching, perspiration and non-biodegradable such as the Brilliant black BN (BB) dye. The purpose of this study is to synthesis the chitosan (CS) and chitosan/activated carbon (CS/AC) composite adsorbent by using solution casting method and to investigate the performance of the resultant adsorbents on removal of BB dye from aqueous solution. Three parameters such as adsorbent dosage, initial dye concentration and contact time were to be identified through batch mode adsorption experiment. The removal efficiency of CS/AC is found to be slightly higher at 97.18 % while CS is 96.14 % at 40 mg/L initial BB dye concentration and 2.5 g adsorbent dosage. The experimental equilibrium data were studied using Langmuir, Freundlich and Temkin isotherms. The Temkin model is found the best to describe the removal of BB dye. Furthermore, pseudo-first order (PFO) kinetic models best fit kinetic studies of adsorption onto composite films. Hence, the CS and CS/AC composite adsorbent films have a capability to remove BB dyes from the wastewater.